Guía práctica para operaciones de M&A: los documentos del proceso previo al SPA y sus secciones más relevantes - Meneses Battifora, Maria Angélica (2023)
The purpose of this article is to enable the reader to understand the key steps prior to the Share Purchase Agreement (SPA) from a target company (seller) to the interested company (buyer). The documents required for this potential transfer have essential characteristics that must be respected throughout the procedure. The author establishes a breaking point in the non-binding and binding nature of the documents, as well as makes special mention of the faculties and obligations of the parties during the negotiations.